Preservation of fruit and vegetable discards with sodium metabisulfite. (15th October 2018) - Ahmadi, F.; Lee, Y.H.; Lee, W.H.; Oh, Y.K.; Park, K.K.; Kwak, W.S.
Abstract: Two series of experiments were performed to investigate the aerobic preservation of fruit and vegetable discards (FVD) using sodium metabisulfite (SMB). In Exp. 1, metabisulfite was applied at 0, 2, 4, 6, and 8 g/kg FVD for 0, 3, 6, 9, and 12 d. Metabisulfite treatment at 6 and 8 g/kg FVD was highly effective in controlling putrefaction and preserving the nutrient components for 6 and 9 d, respectively. In the pilot-scale experiment (Exp. 2), SMB was applied at 0 and 8 g/kg FVD in a 600-L bucket for 0, 6, and 9 d in an outdoor environment. The SMB treatment was highly effective in maintaining the integrity and freshness of FVD, suppressing microbial proliferation, and preserving the nutrient constituents. Under the conditions of this study, SMB effectively preserved FVD in an aerobic environment, enabling their more efficient long-term recycling through livestock feed or development of value-added products. Highlights: Sodium metabisulfite was used for the preservation of fruit and vegetable discard. Metabisulfite effectively preserved nutrient components in an aerobic environment. The effectiveness of metabisulfite was demonstrated in a pilot-scale experiment. No evidence of spoilage was seen in biomass treated for 9 d with metabisulfite. Metabisulfite treatment effectively preserved the antioxidant capacity.